Halligan’s Love Affair with Food - Anne Holden Rønning (Coolabah, 2011)
Marion Halligan’s non-fiction Eat My Words, (1990), Cockles of the Heart (1996) and The Taste of Memory (2004) all have food as their main topic. Travelling round Europe on culinary journeys and staying in hotels and flats she provides us, as readers, with a wealth of recipes and reflections on the role food plays in people’s lives, socially and culturally. This article will discuss some few of the points Halligan raises as she comments on the pleasure of food; on bricolage, both in the finished product and in cookery books; and the language we use to describe food and its processes. Adopting a bicultural approach Halligan compares Australian foods of today with those of her childhood, thus turning these food books into a kind of autobiography.